Inaugural Convocation (Institutional Knowledge at Singapore Management University, 2000)
Entrance to the marquee tent for the inaugural convocation ceremony marking the opening of Singapore Management University and the beginning of the academic year. Ceremonies were held 29 July 2000 at Bras Basah Park, the site of the university’s future city campus.